3D printing and enzyme immobilization: An overview of current trends - Remonatto, Daniela [UNESP] (2023)
Given their enormous flexibility and freedom of design, 3D printing technologies have been applied in various fields, such in the production of high value-added products via biocatalysis. By combining the ease of construction of additive manufacturing with the characteristic selectivity of enzymatic processes, 3D printing offers a series of novel possibilities that have streamlined the screening of fundamental parameters for optimization of enzyme immobilization and process sustainability. This review aimed to examine scientific studies published on the topic between 2016 and 2023 and assess the most critical factors determining the use of 3D printing technologies in the manufacture of enzyme immobilization supports. A discussion is presented on the main advantages and opportunities of commonly used 3D printing techniques and raw materials, as well as on support geometry and chemical functionalization methods. In the current literature, there is great interest in combining the benefits of 3D printing technologies and moldable raw materials for the development of reinforced biopolymers with improved mechanical properties and minimal environmental impacts.